literatur review AGRICULTURAL EDUCATION: UTILIZATION OF AGRICULTURAL WASTE: AGRICULTURAL WASTE - Dewi, Dewi Rakhma (IJBLE Scientific Publications Community Inc., 2020)
The purpose of writing this article is to to describe some of the functions of waste. Waste is the residue or by-product of the main product. Agricultural waste is part of agricultural plants above the ground or part of the shoots, stems that are left after being harvested or the main product is taken and is an alternative feed used as animal feed. The purpose of writing this article is to to describe some of the functions of waste. The method used in this research is literatur review. Based on the results of literature reviews of several agricultural books, most of the rice straw is used as compost. The percentage of rice straw is 65% is composted and 35% is used for animal feed. Agricultural waste is waste that comes from agricultural activities in a broad sense (agriculture, animal husbandry, fisheries and forestry) and agriculture-based industrial activities (agro-industry) in the form of solid waste (plant residues, leaves, animal waste) or liquid waste.